1996
DOI: 10.1161/01.res.78.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte Enhancer Binding Factor-2 Expression and Activity in Vascular Smooth Muscle Cells

Abstract: Proliferation and phenotypic modulation of smooth muscle cells (SMCs) are major components of the vessel's response to injury in experimental models of restenosis. Some of the growth factors involved in restenosis have been identified, but to date little is known about the transcription factors that ultimately regulate this process. We examined the expression of the four members of the myocyte enhancer binding factor-2 (MEF2) family of transcription factors in cultured rat aortic SMCs (RASMCs) and a rat model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 51 publications
5
78
0
Order By: Relevance
“…Here, we hypothesize that alterations in the Myocd splice variant balance are part of the VSMC-mediated response to vascular injury, possibly enhancing the expression of MEF2 target genes ( Figure 7C). Importantly, Firulli et al 39 have previously identified that MEF2A, MEF2B, and MEF2D are abundantly expressed in neointimal VSMCs of rat restenotic tissue, whereas Creemers et al 20 identified that MEF2 dose-dependently titrates MYOCD_v1 protein from interaction with SRF. As such, a reduction in Myocd expression coupled with a decreased interaction with SRF could be required to activate gene expression profiles that drive arterial repair.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we hypothesize that alterations in the Myocd splice variant balance are part of the VSMC-mediated response to vascular injury, possibly enhancing the expression of MEF2 target genes ( Figure 7C). Importantly, Firulli et al 39 have previously identified that MEF2A, MEF2B, and MEF2D are abundantly expressed in neointimal VSMCs of rat restenotic tissue, whereas Creemers et al 20 identified that MEF2 dose-dependently titrates MYOCD_v1 protein from interaction with SRF. As such, a reduction in Myocd expression coupled with a decreased interaction with SRF could be required to activate gene expression profiles that drive arterial repair.…”
Section: Discussionmentioning
confidence: 99%
“…Western blots were performed as described previously (24). Briefly, cells were lysed in cracking buffer, and equivalent quantities of total cellular protein were separated by SDS-PAGE and transferred to nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
“…The polyclonal rabbit anti-MEF2A antibody was purchased from Santa Cruz Biotechnology. The polyclonal anti-MEF2D (kindly provided by Ron Prywes, Columbia University) and anti-MEF2C antibodies have been described (24). Monoclonal anti-NCAM and ␣-tubulin were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…One of the factors whose genetic ablation causes morphological and transcriptional abnormalities during early cardiogenesis is MEF2C. It is a member of the small MEF2 family of MADS-box containing transcription factors that have been implicated in several fundamental processes including myogenesis, fibertype specification, cardiac hypertrophy, atherosclerosis, and as both an activator and inhibitor of apoptosis (Molkentin et al, 1995;Woronicz et al, 1995;Firulli et al, 1996;Kolodziejczyk et al, 1999;Mao et al, 1999;Youn et al, 1999;Okamoto et al, 2000;Passier et al, 2000;Wu et al, 2000;Dunn et al, 2001;Yan et al, 2001). Deletion of the mef2c gene results in a heart with a small, nonlooping LV, loss of the RV, no trabeculation, and decreased expression of several cardiac-specific genes (Lin et al, , 1998Bi et al, 1999;Bruneau et al, 2000;Liu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%